Analisa Kebutuhan Sistem Informasi Akademik Sekolah Dasar - Enjang Yusup Ali; Ali Sudin; Dede Tatang Sunarya; Cucun Sunaengsih (Universitas Pendidikan Indonesia, 2022)
This study aims to identify the need for an easy-to-implement academic information system in elementary schools so that its use can be optimal for school development. This research is a survey research and interviews conducted with school principals and elementary school teachers in Sumedang District, data were collected through questionnaires and in-depth interviews. One of the applications of management information systems in elementary schools is through an academic system to create elementary schools that are able to provide quality academic services to their stakeholders. However, the application of information systems with the design of academic information systems has not been fully implemented in elementary schools. With this research, it is hoped that it will bring up a recommendation for an elementary school academic information system which can later be used as the basis or basis for designing an academic application that can be used by elementary schools to provide quality services for all stakeholders.